2019
DOI: 10.1038/s41598-019-44707-0
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic recordings and modeling under seasonally varying sea ice

Abstract: Acoustic data from the Canada Basin Acoustic Propagation Experiment are discussed. These recordings were obtained under seasonally varying sea ice to the north of Alaska during a period of 154 days. They contain signals from sources that were deployed at ranges of 17.5, 29.6, and 237.8 km and ambient sounds from marine mammals and ice-related events. After the area was covered with ice, the amplitude of receptions from the most distant source gradually decreased as scattering features on the underside of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Collis et al (2016) benchmarked such a model against an elastic normal mode code and wave number integration solution and demonstrated the PE model's ability to compute transmission loss under a slowly varying range-dependent ice thickness. Collins et al (2019) was further able to demonstrate scattering from a data-derived ice surface with keels using a fully elastic PE code over a model range of 40 km. Diachok (1976) showed that a pressure release rough surface could do a good job of matching data, provided the statistics of the keels were well known.…”
Section: Modellingmentioning
confidence: 95%
See 2 more Smart Citations
“…Collis et al (2016) benchmarked such a model against an elastic normal mode code and wave number integration solution and demonstrated the PE model's ability to compute transmission loss under a slowly varying range-dependent ice thickness. Collins et al (2019) was further able to demonstrate scattering from a data-derived ice surface with keels using a fully elastic PE code over a model range of 40 km. Diachok (1976) showed that a pressure release rough surface could do a good job of matching data, provided the statistics of the keels were well known.…”
Section: Modellingmentioning
confidence: 95%
“…In the Canadian Arctic, the Canada Basin Acoustic Propagation Experiment (CANAPE) recently concluded, with early results demonstrating the effect of the Beaufort Gyre throughout the year on propagation between the central Arctic and the Chukchi Shelf (Worcester 2015;Ballard et al 2017). Analysis from these recent data sets will push the underwater acoustics community to advance low-frequency, under-ice propagation models (Collins et al 2019), ocean acoustic-coupled models (Duda et al 2018;Ballard et al 2017), and three-dimensional propagation models. These advances will better allow the modelling of anthropogenic activity, namely, shipping and oil and gas exploration, in the Canadian Arctic.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Effective approaches have been developed for handling sloping solid-solid interfaces and sloping solid boundaries. 3 Some progress has been made in the treatment of sloping fluid-solid interfaces, [4][5][6] but there is a need for improvement in this area. In this paper, several approaches for handling sloping fluid-solid interfaces are discussed and tested, including an approach based on modeling part of a fluid layer as a solid material with low shear wave speed.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are times when increases in normalized ANL, such as around day 25, do not have a corresponding increase in IDM. Some alternate source like other types of cryogenic activity (Collins et al 2019) or biological activity may be affecting some frequencies of the ambient sound at this time. It is interesting to note that ice is more of a distributed source or a plane source than a point source.…”
Section: Spacial Correlation Across Shru(s)mentioning
confidence: 99%